Numerical simulation of fracture reorientation during hydraulic fracturing in perforated horizontal well in shale reservoirs. Issue 15 (3rd August 2018) - Li, Qingchao; Li, Yudi; Cheng, Yuanfang; Li, Qiang; Wang, Fuling; Wei, Jia; Liu, YuWen; Zhang, Chuang; Song, Benjian; Yan, Chuanliang; Ansari, Ubedullah
ABSTRACT: Fracture reorientation affects hydraulic fracturing much in perforated wells. A finite element model used for investigating fracture reorientation is established using the extended finite element method with ABAQUS software. Based on this, both fracture reorientation and fracture propagation during fracturing operation in shale reservoirs are analyzed. Meanwhile, the effect of the difference between the maximum and minimum principal stresses on fracture reorientation during fracturing in shale reservoirs has also been studied. The results demonstrate that the fracture reorients to the direction of the maximum principal stress gradually, and the difference between the maximum and minimum principal stresses impacts the fracture reorientation more than fracture propagation.